2023
DOI: 10.3390/diagnostics13243670
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge to Stabilize, Extract and Analyze Urinary Cell-Free DNA (ucfDNA) during Clinical Routine

Ivonne Nel,
Carolin Münch,
Saikal Shamkeeva
et al.

Abstract: Background: The “Liquid Biopsy” has become a powerful tool for cancer research during the last decade. Circulating cell-free DNA (cfDNA) that originates from tumors has emerged as one of the most promising analytes. In contrast to plasma-derived cfDNA, only a few studies have investigated urinary cfDNA. One reason might be rapid degradation and hence inadequate concentrations for downstream analysis. In this study, we examined the stability of cfDNA in urine using different methods of preservation under variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Research has shown significantly higher levels of urine cfDNA (ucfDNA) in patients with urinary tumors compared to healthy individuals ( Nikanjam et al, 2022 ). Nevertheless, the clinical application of ucfDNA is relatively rare, possibly due to its sensitivity to environmental conditions (e.g., temperature and pH level of preservation solution) ( Kim et al, 2023 ; Ruppert et al, 2023 ), which makes it easier to degrade rapidly, resulting in inadequate concentrations for downstream analysis ( Nel et al, 2023 ) compared to blood-derived cfDNA. Therefore, the weaker stability makes ucfDNA analysis more susceptible to complex preanalytical variables, highlighting the importance of establishing a consensus on ucfDNA experimental procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown significantly higher levels of urine cfDNA (ucfDNA) in patients with urinary tumors compared to healthy individuals ( Nikanjam et al, 2022 ). Nevertheless, the clinical application of ucfDNA is relatively rare, possibly due to its sensitivity to environmental conditions (e.g., temperature and pH level of preservation solution) ( Kim et al, 2023 ; Ruppert et al, 2023 ), which makes it easier to degrade rapidly, resulting in inadequate concentrations for downstream analysis ( Nel et al, 2023 ) compared to blood-derived cfDNA. Therefore, the weaker stability makes ucfDNA analysis more susceptible to complex preanalytical variables, highlighting the importance of establishing a consensus on ucfDNA experimental procedures.…”
Section: Introductionmentioning
confidence: 99%